Pkc1 acts through Zds1 and Gic1 to suppress growth and cell polarity defects of a yeast eIF5A mutant - Zanelli, Cleslei Fernando [UNESP]; Valentini, Sandro Roberto [UNESP] (Genetics Soc Am, 2005)
eIF5A is a highly conserved putative eukaryotic translation initiation factor that has been implicated in translation initiation, nucleocytoplasmic transport, mRNA decay, and cell proliferation, but with no precise function assigned so far. We have previously shown that high-copy PKCI suppresses the phenotype of tif51A-1, a temperature-sensitive mutant of eIF5A in S. cerevisiae. Here, in an attempt to further understand how Pkc1 functionally interacts with eIF-5A, it was determined that PKCI suppression of tif51A-1 is independent of the cell integrity MAP kinase cascade. Furthermore, two new suppressor genes, ZDS1 and GIC1, were identified. We demonstrated that ZDS1 and ZDS2 are necessary for PKC1, but not for GIC1 suppression. Moreover, high-copy GIC1 also suppresses the growth defect of a PKCI mutant (stt1), suggesting the existence of a Pkc1-Zds1-Gic1 pathway. Consistent with the function of Gic1 in actin organization, the tif51A-1 strain shows an actin polarity defect that is partially recovered by overexpression of Pkc1 and Zds1 as well as Gic1. Additionally, PCL1 and BNI1, important regulators of yeast cell polarity, also suppress tif51A-1 temperature sensitiviiy Taken together, these data strongly Support the correlated involvement of Pkc1 and eIF5A in establishing actin polarity, which is essential for bud formation and G1/S transition in S. cerevisiae.